(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
The analysis of the word plays in Plautus ’ comedy Mostellaria, "The Haunted House” which are based on words with different, but yet very similar spelling or sound shows that when these words are derived from the same root, their relation is much deeper than figura etymologica. The analysis also implies that the presence or the absence of etymological connection of the words involved in the pun could be related to the fact whether the word play is about combining two thoughts as two aspects of one idea or about two opposite ideas.